2007
DOI: 10.1007/s10560-007-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic Summer Weekend Camp for Grieving Children: Supporting Clinical Practice Through Empirical Evaluation

Abstract: Through collaborative action-oriented community research, agencybased clinicians, and university-based researchers engaged in a two-year theorydriven evaluation of a therapeutic summer camp for grieving children. The evaluation examined the camp practice model and children's engagement in therapeutic camp activities and psychosocial functioning based on the camp staff and parental caregivers' assessments. The first year findings led to a synergistic decision-making process that strengthened one of camp therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The current study explored what intervention strategies were most impactful for the campers. Though there are some previous studies with qualitative components examining the impact of grief camps for children and teens (Barrett, 2004;Creed et al, 2001;Farber & Sabatino, 2007;Loy, 2000;Nabors et al, 2004), these studies showed mixed results and/or neglected to interview the children themselves. Also, this study differs from other studies that have used qualitative measures to explore grief camps by interviewing the children at least 3 months after the experience and not immediately following the camp sessions, allowing the campers some time to process the experience and its long-term impact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study explored what intervention strategies were most impactful for the campers. Though there are some previous studies with qualitative components examining the impact of grief camps for children and teens (Barrett, 2004;Creed et al, 2001;Farber & Sabatino, 2007;Loy, 2000;Nabors et al, 2004), these studies showed mixed results and/or neglected to interview the children themselves. Also, this study differs from other studies that have used qualitative measures to explore grief camps by interviewing the children at least 3 months after the experience and not immediately following the camp sessions, allowing the campers some time to process the experience and its long-term impact.…”
Section: Discussionmentioning
confidence: 99%
“…A mixed methods approach to evaluating the camp was applied. Children who attended one of the camp sessions showed an increase in problems in psychosocial functioning as measured by a quantitative instrument, whereas campers attending a second camp session showed a decrease in problems with psychosocial functioning (Farber & Sabatino, 2007). The limitations of the study included instruments that had not been validated, as well as a lack of a control or comparison group.…”
Section: Interventionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Brief weekend camps for bereaved children have been available since the early 1990s (Sorensen and King, 1999) and their prevalence and quality has continued to expand. Farber and Sabatino (2007) used Likert scales to rate children’s involvement and their psychosocial functioning when examining their camp sessions, but findings were inconclusive. No direct verbal input was provided from the children in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Young children may show signs of regressive behaviours (Farber & Sabatino, 2007;Schoen, Burgoyne & Schoen, 2004). This may be an attempt to reclaim a time of safety or security on the part of the child, before the disruption due to loss occurred.…”
mentioning
confidence: 99%